Syndicate [large type] - Francis, Felix; Francis, Dick (Francis, Felix. Dick Francis novel, 2024)
"Chester Newton has built his fortune organizing racehorse syndicates, where top horses are co-owned an managed by several parties. These joint enterprises are high risk and high reward--and the stakes only get higher as the syndicates grow larger. After an anxious morning waiting for the results of the Epsom Derby, the premier flat race in the UK, Chester has an afternoon of triumph--and an evening of total terror. Someone tries to take over on of the syndicates by force--and by threats to him and his family. For the first time in Chester's life it's not just money at stake--it's his life and the lives of his loved ones"--